1978
DOI: 10.1002/app.1978.070220311
|View full text |Cite
|
Sign up to set email alerts
|

Specific hydroxide ion catalysis of the endwise depolymerization of cellulose

Abstract: SynopsisThe endwise depolymerization (unzipping reaction) of hydrolyzed cotton cellulose ( x = 200) in water under a nitrogen atmosphere was followed a t 98OC at several alkalinities in the pH range of 8.0-10.5. The observed apparent first-order rate constant k l was invariable at low alkalinity (kl = ko), while above pH 8.5, kl increased with pH. The data conform with the expressionwhere [SH] denotes substrate concentration. The specific hydroxide ion catalysis is considered to involve ionization of the anome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Similarly, our previous study has also showed that 10% Ni/ZrO 2 was largely ineffective at promoting H 2 production during cellulose pyrolysis at low temperatures ( ≤773 K) when used in isolation, resulting in significant tar formation [12] . The results of these intermediate studies therefore implies that the inclusion of Ca(OH) 2 forms smaller, more linear oxygenated intermediates in the range of C 4 -C 6 [36] that are more readily reformed by the 10% Ni/ZrO 2 to H 2 .…”
Section: Analysis Of the Compounds Formed During The Att Of Cellulosementioning
confidence: 87%
“…Similarly, our previous study has also showed that 10% Ni/ZrO 2 was largely ineffective at promoting H 2 production during cellulose pyrolysis at low temperatures ( ≤773 K) when used in isolation, resulting in significant tar formation [12] . The results of these intermediate studies therefore implies that the inclusion of Ca(OH) 2 forms smaller, more linear oxygenated intermediates in the range of C 4 -C 6 [36] that are more readily reformed by the 10% Ni/ZrO 2 to H 2 .…”
Section: Analysis Of the Compounds Formed During The Att Of Cellulosementioning
confidence: 87%
“…In base and oxidative hydrolysis, cellulose was depolymerized via endwise chain cleavage, which can consume reducing ends and do not form new reducing ends. 33 The increase of reducing ends in the solution strongly suggests that the cellulose is depolymerized by the acid hydrolysis mechanism.…”
Section: Cellulose Depolymerization In Bmimclmentioning
confidence: 99%
“…The major termination reaction (steps v-vi, Scheme 14) has an activation energy of 134 kcal/mol, higher than that of peeling (100 kcal/ mol), 147 and can thus be mitigated using mild reaction temperatures ( Table 5, entry 1). At 95°C and [HO -] 0 ≥ 1.25 M, for example, the termination reaction is estimated to be about 100 times slower than peeling, 149 though the ratio can span more than an order of magnitude. 147 Nevertheless, termination competes with peeling even at low temperature.…”
Section: Cellulose Conversionmentioning
confidence: 99%
“…Alkalinity also affects the relative rates of peeling and termination (entry 2). In the case of cellulose degradation in aqueous sodium hydroxide at low [HO -] 0 , R peel /R term is approximately constant, 149 but conversion increases with [HO -] 0 , 149,150 implicating physical termination as a conversion-limiting factor at low [HO -] 0 . Interestingly, when Ba 2+ or Sr 2+ is used as the counterion, the conversion decreases with increasing alkalinity in the range 0.1 M £ [HO -] 0 £ 0.4 M. 150 In more basic solution, cellulose conversion reaches a maximum at [NaOH] 0 = 6 M, the concentration at which cellulose swelling is maximized.…”
Section: Cellulose Conversionmentioning
confidence: 99%